MEKANISME PEMBERDAYAAN MASYARAKAT MELALUI BADAN USAHA MILIK DESA DELTA MULIA DI DESA PANEMPAN PADA MASA PANDEMI COVID-19: (Suatu Studi Mekanisme Model dalam Pemberdayaan Masyarakat) - Hardi Warsono; Fathir Adhitya Hidayat (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Since the COVID19 pandemic, society empowerment accomplished by Village-Owned Enterprises (BUM Desa) requires people to addressing their activity follow the changes. The empowerment mechanism carried out by BUM Desa Delta Mulia in order to face obstacles of this pandemic is quite different due to huge requirement preparation and standardization according to Government order. The aim of this research is to know the preparation model and process for empowerment society that has been done by BUM Desa Delta Mulia during COVID19 pandemic. The method is carried out by descriptive method with qualitative approach. Interview, observation, and documentation data are collected. The data source is taken from BUM Desa Delta Mulia officer. Data reduction, display, and conclusion are the way to analyze data. During the process, verification is done by author. The results show that the empowerment model mechanism conducted by BUM Desa Delta Mulia during COVID19 pandemic in the point of view preparation and the process of empowerment are good and well-standardized based on request and health protocol. However, there are some disobedient of people ignoring the protocol that had delivered by government and BUM Desa Delta Mulia.